Prenatal intrauterine maxillary development — An evaluation with three-dimensional ultrasound - Grill, Florian D.; Behr, Alexandra V.; Rau, Andrea; Ritschl, Lucas M.; Roth, Maximilian; Bauer, Franz X.; Wolff, Klaus Dietrich; Esser, Tilman; Loeffelbein, Denys J. (Journal of Cranio-Maxillofacial Surgery, 2019)
Objectives: The aim of this prospective study was to investigate normal fetal maxillary development with volume ultrasound during the prenatal phase, for a better estimation of maxillary growth processes. Methods: Some 210 3D volumes were obtained in two measurement series from 38 healthy women (gestational age: 19+2 to 31+4 weeks) using a GE Voluson™ E10 ultrasound system. Maxillary length and width were determined in the axial and sagittal planes. Clearly defined, reproducible landmarks were used for measurements. The results were correlated with gestational age and compared with previously reported studies. Results: Total maxillary length ranged from 10.30 to 24.75 mm, total maxillary width from 13.65 to 37.30 mm in an observation period during the second trimester, with high reproducibility for all landmarks. All evaluation results showed steep growth with exponential character. Length growth was determined to be more dominant than width growth. Intra-rater correlation was evaluated to be almost perfect (ICC (3) > 0.8). Conclusion: This study presents measurements of physiological fetal maxillary development. The defined landmarks proved to be representative for further investigations. This study serves as a baseline for a better understanding of fetal maxillary growth processes, and may be useful for standardising detection of malformations or intrauterine growth restrictions.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Maxillary growth; Prenatal palatal development; Three-dimensional sonography